Grain size, geochemical characteristics, and transport patterns of surface sediments in the Dongsha sea area, South China sea - Wang, Anqi; Yu, Honggang; Tian, Xu; Zhu, Zichen; Xu, Guoqiang; Zhang, Zhiwei; Mai, Fahai (Frontiers in Earth Science, 2026)
This study conducted a comprehensive analysis of grain size, major elements, and rare earth elements (REEs) in 34 surface sediment samples from the Dongsha area of the South China Sea to reveal their characteristics and material sources. Grain size analysis indicates that sedimentary processes are jointly controlled by inputs from multiple sources and complex hydrodynamic conditions. End-member modeling identified three main components corresponding to distantly transported riverine clay, riverine fine silt, and proximal shelf coarse clastics. Sediment transport predominantly occurs along northeast-southwest and northwest-southeast trends. The major element composition is primarily Al2O3, followed by CaO, indicating a primarily terrigenous clastic origin with minimal contributions from marine biogenic processes and authigenic sedimentation. The REE distribution patterns, characterized by light REE (LREE) enrichment, moderate negative Eu anomalies, and no Ce anomalies, support a predominantly terrigenous origin. Comprehensive provenance analysis demonstrates a high geochemical affinity between the sediments and materials derived from Taiwan, with a minor contribution from the Pearl River. Therefore, Taiwan is the dominant source of surface sediments in the study area, and the Pearl River is a secondary source. These findings provide a critical basis for understanding sedimentary processes and material transport mechanisms in the Dongsha area of the South China Sea.